Reducing repeat imaging in hepato-pancreatico-biliary surgical cancer care through shared diagnostic imaging repositories. Issue 1 (January 2019) - Hallet, Julie; Coburn, Natalie G.; Alberga, Amanda; Fu, Longdi; Tharmalingam, Sukirtha; Beyfuss, Kaitlyn; Milot, Laurent; Law, Calvin H.L.
Abstract: Background: With regionalization of care, patients often undergo treatment in institutions other than where the initial investigation is conducted. This study assessed the impact of a shared diagnostic imaging repository (SDIR) on processes of care and outcomes in hepato-pancreatico-biliary (HPB) cancer surgery. Methods: Provincial administrative datasets were linked to study HPB cancer patients operated at a regional cancer centre (2003–2014). SDIR and non-SDIR groups were based on where initial imaging (CT or MRI) was conducted. Outcomes were repeat imaging before surgery and wait times for surgery from initial imaging and surgical consultation. Results: Of 839 patients, 474 were from SDIR institutions. Fewer SDIR patients underwent any repeat imaging (55.9% vs. 75.3%; p < 0.01) and repeat imaging with same modality and protocol (24.7% vs. 43.0%; p < 0.01). Median wait time to surgery from initial imaging (64 Vs. 79 days; p < 0.01) and surgical consultation (39 Vs. 45 days; p = 0.046) was shorter with SDIR. SDIR patients had lower adjusted odds of any repeat imaging (OR 0.20 [0.14–0.30]), and repeat imaging with same modality and protocol (OR 0.58 [0.41–0.80]). Conclusion: Radiology sharing with SDIR reduced repeat imaging for HPB cancer surgery, including potentially redundant repeat imaging with same protocol, and shortened wait time to surgical care.